Therapeutic aspects of Tulsi unraveled: A review - Naveen Srinivas; Ketki Sali; Atul A Bajoria (Wolters Kluwer Medknow Publications, 2016)
Introduction: The purpose of the paper was to review the diverse pharmaceutical aspects of Tulsi. Materials and Methods: Several publications and books were electronically searched in google using the keywords "Tulsi as a medicine," "Tulsi as a medicinal plant," "Medicinal properties of Ocimum sanctum," and "Tulsi in dentistry." The search was limited to articles and books in the English literature. To prepare a thorough review on the therapeutic aspects of Tulsi, the contents were screened between the year 1985 to 2015 by going through the title and abstracts, and further shortlisting articles for full text reading. Conclusion: The present review revealed that Tulsi has an extensive array of medicinal uses, as evidenced by various studies conducted, but its use in allopathic medicine is still limited because of the lack of clinical trials on humans.